Handbook of pediatric surgery - Buicko, Jessica L. (Wolters Kluwer, 2019)
"Publisher's Note: Products purchased from 3rd Party sellers are not guaranteed by the Publisher for quality, authenticity, or access to any online entitlements included with the product. Written by residents for residents and medical students, Handbook of Pediatric Surgery is a pocket-sized resource filled with must-know information for the pediatric surgery rotation. In a concise, easy-to-reference format, it covers management of the pediatric surgical patient, pediatric trauma surgery, common pediatric surgical problems, and pediatric surgical oncology. A highly templated, bulleted content makes it quick and easy to find key information when you need it. Chapters on surgical problems clearly present historical background, relevant anatomy, epidemiology and etiology, clinical presentation, diagnosis, surgical management, and postoperative care. Additional chapters cover evaluation and examination, pediatric anesthesia, common pediatric drug dosing, and more. Succinct overviews of each topic include clinical pearls and pitfalls and algorithms where appropriate. Enrich Your eBook Reading Experience with Enhanced Video, Audio and Interactive Capabilities! Read directly on your preferred device(s), such as computer, tablet, or smartphone Easily convert to audiobook, powering your content with natural language text-to-speech Adapt for unique reading needs, supporting learning disabilities, visual/auditory impairments, second-language or literacy challenges, and more"--